PENGARUH SERVANT LEADERSHIP DAN EMPOWERMENT TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOUR PADA KARYAWAN ASA VILLA SEMINYAK - Pratama Sandara, Putu Agung; Suwandana, I Gusti Made (E-Jurnal Manajemen, 2018)
ABSTRACT The research paper aims to examine the effect of servant leadership and empowerment on organizational citizenship behavior on Asa Villa Seminyak employee, using census method (total sampling) in determining the sample of 44 respondents, Through multiple linear regression analysis technique. The result of analysis proves that servant leadership and empowerment of positive effect simultaneously on organizational citizenship behavior. Servant leadership has a positive effect partially on organizational citizenship behavior. Empowerment has a positive effect partially on organizational citizenship behavior. Asa Villa Seminyak management side must prioritize the implementation of servant leadership in order to create a safe and comfortable atmosphere in work. Management through the leadership to implement empowerment application with ease for employees in finding important information related to the job so as to be able to complete the work.   Keywords : servant leadership, empowerment, organizational citizenship behavior